PERANCANGAN SISTEM INFORMASI PEMBAYARAN BEROBAT PASIEN DI KASIR KLINIK SANGRILA JAKARTA SELATAN - Nasril, Nasril; Sudirman, Sudirman; Subagiyo, Subagiyo; Kuswandi, Kuswandi; Hariyanto, Hariyanto (JURNAL LENTERA ICT, 2021)
Design and build a payment system for patient treatment at the Sangrila Clinic at PT Prima Hexa Taslam, South Jakarta. This study uses a descriptive method, which describes and analyzes data based on existing facts and information. The data collection technique used is by conducting field studies which include observations, interviews, and literature studies. Based on the results of the study, it was concluded that Sangrila Clinic still uses a manual system in carrying out the medical record data collection process. This creates several obstacles, namely: employee delays in recording all medical record reports because it is still done manually. The research method used is Library Research and Field Research, the application software used is Microsoft Visual Studio 2010 Ultimate, Microsoft SQL Server Management Studio 2008 R2, Microsoft Word 2019, SAP Crystal Reports, Microsoft Visio 2019, Microsoft Power Point 2019, Google Chrome, and Adobe Photoshop 2015.Keywords: Design, System, Information, Medical Records, Patients.